2019
DOI: 10.1186/s12887-019-1860-5
|View full text |Cite
|
Sign up to set email alerts
|

The maternal antibody against diphtheria, tetanus and pertussis showed distinct regional difference in China

Abstract: Background: Passive transferred antibodies to the fetus play an essential role on protecting neonates and young infants until infant vaccination is more efficacious. However, very little is known about the discrepancy of DTP vaccine associated antibodies level in neonates from different economic areas in China. Methods: In 2018, 200 neonates hospitalized in Shunyi Women and Children's Hospital in Beijing, and 238 neonates hospitalized in Qianjiang Central Hospital located in the southwestern mountainous areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…[16][17][18] In a study conducted in China, the anti-PT level was found below 40 IU/mL in 98.4% of pregnant women. 3 In another study conducted in 2 different regions in China, anti-PT level was found below 40 IU/mL in 96.3% of pregnant women and 97.4% of cord blood. 17 In Spain, the anti-PT level in the postnatal cord blood of 353 pregnant women was found to be below 40 IU/mL in 90%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[16][17][18] In a study conducted in China, the anti-PT level was found below 40 IU/mL in 98.4% of pregnant women. 3 In another study conducted in 2 different regions in China, anti-PT level was found below 40 IU/mL in 96.3% of pregnant women and 97.4% of cord blood. 17 In Spain, the anti-PT level in the postnatal cord blood of 353 pregnant women was found to be below 40 IU/mL in 90%.…”
Section: Discussionmentioning
confidence: 92%
“…D espite the availability of effective vaccines against pertussis, the prevalence and severity of the disease continue to maintain its importance. [1][2][3] In recent years, reasons for the increased prevalence of pertussis include developments in diagnostic methods, the transition from whole-cell vaccine to acellular vaccine in national immunization programs (NIPs) and the fact that the vaccine and pertussis disease do not provide long-term immunity. In newborns and infants, the absence of protective antibodies in the first months and inadequate transplacental antibodies from the mother leave infants vulnerable to pertussis because primary vaccination can be performed at the earliest at the 6th week.…”
mentioning
confidence: 99%
“…Anti-TT IgG antibodies were quantified using commercial ELISA kits (Euroimmun, Lübeck, Germany), and the results were expressed in international units per milliliter (IU/ml). Based on the manufacturer’s guidelines and previous studies, 17 , 20 results were categorized into four tiers: <0.01 IU/ml (seronegative), 0.01 – <0.1 IU/ml (basic immunity), ≥0.1 IU/ml (seroprotective), >0.5 IU/ml (long-term protection).…”
Section: Methodsmentioning
confidence: 99%
“…During 2017-2020, pertussis cases were still detected across several regions, with Chongqing identified as a high-high cluster area (Figure S8 in Multimedia Appendix 1). Recent studies have found that a substantial proportion of the population is susceptible to pertussis due to vaccination and regional discrepancies in protective antibody rates, suggesting the need for introducing a booster to protect children [33,34]. By contrast, the incidence of neonatal tetanus continued to decrease in almost all the provincial units (Figure S9 in Multimedia Appendix 1).…”
Section: Vaccine-preventable Diseasesmentioning
confidence: 99%